2004
DOI: 10.1021/cm035306u
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating of Nanocrystalline CoFeNi Soft Magnetic Thin Films from a Stable Citrate-Based Bath

Abstract: CoFeNi alloys are some of the most studied soft magnetic materials because of their superior properties over FeNi alloys as write head core materials in hard-disk-drives. Electroplating processes have major significance in the fabrication of thin-film recording heads due to their advantages of simplicity, cost-effectiveness, and controllable patterning. Conventional low pH (2.5-3.0) baths suffer from problems such as poor stability, low current density efficiency, and voids in deposited films due to the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…In our previous study for the citric acid, both the current efficiency and the Fe content decreases with increasing the concentration of the citric acid [5]. In contrast, both the current efficiency and the Fe content show almost constant values except for 0 g/L of NH4Cl, indicating that we can vary the concentration of NH 4 Cl without the change in the Fe content. The current efficiency of approximately 95% is much higher than those for our previous study (85%) [5] and other researcher's ones (60 -80%) [10][11].…”
Section: B Measurementsmentioning
confidence: 75%
See 4 more Smart Citations
“…In our previous study for the citric acid, both the current efficiency and the Fe content decreases with increasing the concentration of the citric acid [5]. In contrast, both the current efficiency and the Fe content show almost constant values except for 0 g/L of NH4Cl, indicating that we can vary the concentration of NH 4 Cl without the change in the Fe content. The current efficiency of approximately 95% is much higher than those for our previous study (85%) [5] and other researcher's ones (60 -80%) [10][11].…”
Section: B Measurementsmentioning
confidence: 75%
“…Osaka et al have been reported Co-Fe-Ni films with high saturation magnetic flux density and low coercivity using ammonium chloride (NH4Cl) [8]. For electroplating of Ni films, the effect of NH 4 Cl on the crystal orientation has been reported [9]. As the orientation is one of factors to determine magnetic properties, we expected an improvement in soft magnetic properties of electroplated FeNi films.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations